1978
DOI: 10.1002/chin.197813023
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: HYDROUS TITANIUM OXIDE AS A CONCENTRATOR FOR TRACE NUCLIDES IN SEAWATER

Abstract: Das Adsorptionsverhalten von 14 im Meerwasser gelösten Radionucliden an hydratisiertem Ti‐oxid wird im pH‐Bereich 0‐8 untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As an example, the immobilization of long-lived 137 Cs (30.17 years half-life) produced by nuclear fission of uranium-235 can be considered. As is shown by Doshi [6], 137 Cs is effectively adsorbed from water onto hydrated titanium dioxide: the distribution coefficient between the liquid and solid phases is 178. Venkataramani [7] has found that sorption of 137 Cs on hydrated titanium dioxide becomes noticeable at pH 4 and increases significantly upon transfer to alkaline medium-at pH 10 sorption is more than 10 times higher than at pH 4.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…As an example, the immobilization of long-lived 137 Cs (30.17 years half-life) produced by nuclear fission of uranium-235 can be considered. As is shown by Doshi [6], 137 Cs is effectively adsorbed from water onto hydrated titanium dioxide: the distribution coefficient between the liquid and solid phases is 178. Venkataramani [7] has found that sorption of 137 Cs on hydrated titanium dioxide becomes noticeable at pH 4 and increases significantly upon transfer to alkaline medium-at pH 10 sorption is more than 10 times higher than at pH 4.…”
Section: Introductionmentioning
confidence: 87%
“…Bignon [1] only studied the composition of film and not its contamination with radionuclides. Some authors [6][7][8][9][10][11] studied sorption of cobalt and caesium radionuclides but either freshly precipitated hydrated titanium dioxide or nanocomposites from hydrated and non-hydrated titanium dioxide were used as sorbents. At the same time, freshly precipitated hydrated titanium dioxide has a large specific surface area (ca.…”
Section: Introductionmentioning
confidence: 99%